Legal Protection Due to Flight Delays Reviewed from Transportation Law in Indonesia - Nandari, Ni Putu Sawitri; Yudas Swastika, I Gusti Bagus; Julia Mahadewi, Kadek; Suderana, I Wayan; Rusmana, I Putu Edi (Faculty of Law, Universitas Pekalongan, 2024)
As an air transport passenger, it is very important to know about the rights as consumers so that when there are irregularities or violations, passengers can demand their rights to be fulfilled. Currently, it is not uncommon in air transportation activities, airlines do not fulfill their obligations as business actors. The problem in this study is what is the legal protection due to flight delays in terms of transportation law in Indonesia? and what efforts can be made by passengers in minimizing flight delays? The research method used in this study is normative legal research with a statutory approach, a fact approach, and a conceptual approach. This research uses primary legal materials and secondary legal materials. The technique of collecting legal materials used in this study was obtained from literature research. In this study, the legal material analysis technique used is a juridical descriptive technique. Preventive legal protection in flight delays is regulated in Article 146 of Law Number 1 of 2009 concerning Aviation. Meanwhile, repressive legal protection in resolving disputes that have arisen due to flight delays is regulated in Article 9 paragraph 1 of the Minister of Transportation Regulation Number 89 of 2015 regulating flight delay compensation. Provisions related to administrative sanctions for business actors who have violated their obligations are regulated in Article 60 paragraph 2 of the Law. Efforts that passengers can make in minimizing delays are by choosing a reliable airline by paying attention to On Time Performance (OTP) as a service standard